A Biblical-Theological Study of Saul’s Kingship in 1 Samuel 9-15 - Fellix Gosal (International Journal of Education, Information Technology, and Others, 2026)
This study analyzes the ascent and decline of Saul in 1 Samuel 9–15 using a narrative-theological framework, emphasizing the transmission of theological significance through narrative rather than through abstract doctrinal expression. By closely looking at how the plot develops, how characters are developed, how dialogue is used, how repetition is used, how irony is used, how narrative time is used, and how the narrator evaluates the story, the study claims that the Saul story is a consistent theological picture of monarchy under divine sovereignty. The results show that Saul's monarchy starts with real divine choice, Spirit enablement, and narrative expectation. This goes against ideas that he was an illegitimate or only temporary ruler. The story also shows a pattern of disobedience caused by fear, confusion about roles, and self-justifying religiosity that eventually hurts Saul's calling. Saul's rejection does not stem from individual failures; rather, it is the climax of a continuous narrative trajectory wherein obedience, trust, and surrender to prophetic authority are supplanted by autonomous leadership. The study concludes that the Saul cycle serves as a foundational narrative theology of kingship, defining obedience to the word of YHWH as the essential criterion for legitimate leadership in Israel and providing lasting theological insight into the interplay between divine election and human responsibility.